Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 43

Answer

x=-7

Work Step by Step

Simplifying 16(x + 3) = 7(x + -5) + -9(x + 4) + -7 Reorder the terms: 16(3 + x) = 7(x + -5) + -9(x + 4) + -7 (3 * 16 + x * 16) = 7(x + -5) + -9(x + 4) + -7 (48 + 16x) = 7(x + -5) + -9(x + 4) + -7 Reorder the terms: 48 + 16x = 7(-5 + x) + -9(x + 4) + -7 48 + 16x = (-5 * 7 + x * 7) + -9(x + 4) + -7 48 + 16x = (-35 + 7x) + -9(x + 4) + -7 Reorder the terms: 48 + 16x = -35 + 7x + -9(4 + x) + -7 48 + 16x = -35 + 7x + (4 * -9 + x * -9) + -7 48 + 16x = -35 + 7x + (-36 + -9x) + -7 Reorder the terms: 48 + 16x = -35 + -36 + -7 + 7x + -9x Combine like terms: -35 + -36 = -71 48 + 16x = -71 + -7 + 7x + -9x Combine like terms: -71 + -7 = -78 48 + 16x = -78 + 7x + -9x Combine like terms: 7x + -9x = -2x 48 + 16x = -78 + -2x Solving 48 + 16x = -78 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 48 + 16x + 2x = -78 + -2x + 2x Combine like terms: 16x + 2x = 18x 48 + 18x = -78 + -2x + 2x Combine like terms: -2x + 2x = 0 48 + 18x = -78 + 0 48 + 18x = -78 Add '-48' to each side of the equation. 48 + -48 + 18x = -78 + -48 Combine like terms: 48 + -48 = 0 0 + 18x = -78 + -48 18x = -78 + -48 Combine like terms: -78 + -48 = -126 18x = -126 Divide each side by '18'. x = -7 Simplifying x = -7
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.